The Prevalence of Rhesus-Negative Blood Group Among Patient With Small Cell Lung Cancer and Analysis of Its Effect on Overall Survival - Biswas, Abhishek; Jiang, Yue; Li, Danmeng; Mehta, Hiren J.; Kaye, Frederic (Frontiers in Oncology, 2018)
A higher incidence of Rhesus group D (RHD)-negative blood group among patients with Small Cell Cancer of the lung (SCLC) had been previously reported but reproducibility was not confirmed, and clinical relevance is undefined. We tested 1090(SCLC; Adenocarcinoma: Squamous=202:536:352) cases of lung cancer over a 3-year period at a single institution and noted a higher frequency RHD negative status among SCLC cases (19/89) compared with non-SCLC (61/480) that could not be explained by differences in ethnic background in the patient population. While we confirmed poor ECOG functional status, advanced stage, elevated alkaline phosphatase, and low albumin levels as independent and significant factors for reduced overall survival (OS), we did not detect any clinical outcome correlations with RHD status in our dataset. Patients with SCLC rarely undergo surgical resection resulting in limited data for blood group analyses. We have now detected a higher rate of RHD-negative status in patients with SCLC compared with all other subtypes of lung cancer. The clinical and biological basis for this observation is undefined and we feel that this may be explained by variations in ethnic background.